Mainstreaming the Water-Energy-Food Nexus through nationally determined contributions (NDCs): the case of Brazil. (7th February 2020) - Paim, Maria-Augusta; Salas, Pablo; Lindner, Sören; Pollitt, Hector; Mercure, Jean-Francois; Edwards, Neil R.; Viñuales, Jorge E.
ABSTRACT: The Water-Energy-Food Nexus approach to the governance of natural resources seeks to identify and address the synergies and trade-offs amongst traditionally separated sectors, to capture significant feedbacks that have so far remained insufficiently understood and regulated. One key specificity of the Nexus approach is the need for intersectoral, cross-scale and stakeholder integration, which is particularly challenging due to the lack of policy coordination prevailing in many countries. Yet, some emerging integrated policy processes, such as those aimed at implementing nationally determined contributions (NDCs) under the 2015 Paris Agreement, may offer a sufficient level of integration to mainstream the Nexus approach. This article focuses on the potential of such NDC processes in Brazil. NDC processes in China, the European Union, India and Mexico are used as indicators associated with higher or lower degrees of integration for a more specific analysis of the case of Brazil. The article concludes that the barriers to sectoral integration raised by the dominant position of the agricultural sector in Brazil as regards, among other things, environmental legislation, are unlikely to be overcome by internal action. This represents a threat to achieving the target of zero deforestation in Brazil, considering the cropland-livestock forestry feedbacks involved in the growing demand for agricultural commodities from China. NDCs already provide space for international cooperation, which could be further developed to include measures for linking demand for agricultural commodities from the EU and China, and massive land-use change and deforestation in Brazil. Key policy insights The NDCs from India, China, EU, Mexico and Brazil recognize, to varying extents, the Nexus approach in their climate policies, particularly the link with water uses in agriculture. The NDCs from EU, Mexico and Brazil include some elaborated Nexus issues related to indirect land use-forestry-agriculture. Sectoral integration could be progressively strengthened under the Nexus approach as part of the five-yearly updates of the NDCs. The NDCs from Brazil and China could provide a policy window to integrate indirect land use-forestry-agriculture collaborative measures, for the purposes of tackling the deforestation trade-off resulting from Brazilian exports of soybeans to China.